A camera calibration method based on two orthogonal vanishing points. (24th July 2013) - Lugang, Zhao; Chengke, Wu; Jifeng, Ning; Xhafa, Fatos; Chen, Xiaofeng; Huang, Xinyi; Kolici, Vladi
SUMMARY A camera calibration method based on the two vanishing points, which are orthogonal to each other, is presented in this paper. On the basis of the facts that the modulus constraint can provide an equation and that two equations can be obtained from two pairs of vanishing points, which are orthogonal to each other, the self‐calibration is quasilinearly realized. The experiment results with simulate data and real image sequences show that the presented method is efficient. Copyright © 2013 John Wiley & Sons, Ltd.